Experimental methods: Extra-laboratory experiments-extending the reach of experimental economics - Charness, Gary; Gneezy, Uri; Kuhn, Michael A. (Journal of economic behavior & organization, 2013)
•We propose a new classification scheme for lab and field experiments.•We describe examples of how different experiments fit into different categories.•We provide organizing principle for classifying research experiments. We propose a new organizing scheme for classifying types of experiments. In addition to the standard categories of laboratory and field experiments, we suggest a new category: “extra-laboratory experiments.” These are experiments that have the same spirit as laboratory experiments, but are conducted in a non-standard manner. We also suggest some organizing principles to distinguish amongst the three types of experiments.